Remarkable Response of Metastatic Gallbladder Carcinoma to Apatinib After Failed Multiline Chemotherapies: A Case Report and Literature Review - Mengxi Zhang; Mengxi Zhang; Pengfei Zhang; Pengfei Zhang; Kexun Zhou; Kexun Zhou; Qiu Li; Qiu Li (Frontiers in Oncology, 2019)
Gallbladder carcinoma (GBC) is a relatively rare and aggressive malignant tumor with a poor prognosis. A systematic review of current clinical studies illustrates an extreme paucity of second-line therapeutic options following the failure of standard-of-care cisplatin-gemcitabine chemotherapy. The efficacy of apatinib, an highly potent and selective oral inhibitor of VEGFR-2 tyrosine kinase, for refractory advanced GBC has not yet been clarified. Herein, we report a case of advanced GBC that presented a durable partial response to apatinib used as monotherapy after the failure of multiline chemotherapies including S-1 monotherapy, capecitabine monotherapy, gemcitabine plus capecitabine, and irinotecan plus oxaliplatin. The patient achieved an efficacy of partial response within 2 months. By September 23, 2019, the duration of treatment had extended for almost 1 year with a satisfactory quality of life, and the administration of apatinib was continued. Dose reduction of apatinib occurred at week four due to grade 2 hypertension and hand-foot skin reaction (HFSR). No fatigue, proteinuria, mucositis, or thrombocytopenia occurred. To the best of our knowledge, this is the first case of a successful use of apatinib monotherapy for heavily pretreated GBC. Further prospective studies are warranted to confirm the efficacy and safety of apatinib in GBC.